Production of Methyl-Iodide in the Environment - Duborská, Eva; Balíková, Katarína; Matulová, Michaela; Zvěřina, Ondřej; Farkas, Bence; Littera, Pavol; Urík, Martin (Frontiers in Microbiology, 2021)
Iodine is an essential micronutrient for most of the living beings, including humans. Besides its indispensable role in animals, it also plays an important role in the environment. It undergoes several chemical and biological transformations resulting in the production of volatile methylated iodides, which play a key role in the iodine’s global geochemical cycle. Since it can also mitigate the process of climate change, it is reasonable to study its biogeochemistry. Therefore, the aim of this review is to provide information on its origin, global fluxes and mechanisms of production in the environment.